PENGEMBANGAN MEDIA PEMBELAJARAN DENGAN APLIKASI MACROMEDIA FLASH PADA MATERI PERUBAHAN WUJUD ZAT TERHADAP MOTIVASI BELAJAR SISWA - Ma’natunnisa Ma’natunnisa; Bq Azmi Syukroyanti; Sukainil Ahzan (Prosiding Seminar Nasional Lembaga Penelitian Dan Pendidikan (LPP) Mandala)
The research aims to develop learning media using macromedia flash applications on the subject of 'substance change'. The research was conducted in odd semester from August to September 2018/2019 school year at Woha 2 Junior High School. This study adopted the Sugiyono development model. The instrument used is a media validation questionnaire and student learning motivation. The results of the development were seen from the media feasibility questionnaire from expert I by 80% 'in the proper category' and expert II in the amount of 92% in the category of 'very decent'. The average results of the validity test of media experts and student learning motivation questionnaire, namely 86% are categorized as 'very feasible'.The results of the trial of 15 students gave very good categories and 4 students gave good grades, therefore there were an average questionnaire of student learning motivation that was 86.05% categorized very well. The study concluded that learning media development products with macromedia flash applications were 'very good'.